MBD2 as a Potential Novel Biomarker for Identifying Severe Asthma With Different Endotypes - Chen, Zhifeng; Yuan, Yu; He, Yi; Wasti, Binaya; Duan, Wentao; Jia, Jingsi; Li, Danhong; Xiao, Bing; Zhang, Dongshan; Ma, Libing; Li, Jianmin; Liu, Yi; et al. (Frontiers in Medicine, 2021)
Abstract Background Studies have shown that methyl-CpG binding domain protein 2 (MBD2) expression is significantly elevated in a neutrophil-dominant severe asthma mouse model. It also regulates Th17 cell differentiation. The objective of this study was to investigate the relationship between serum MBD2 levels in patients with severe asthma with different endotypes. Methods Eligible adults with confirmed asthma (n = 63) underwent a clinical assessment, asthma control test and pulmonary function test and were classified as having mild, moderate or severe asthma. Severe asthma endotypes were defined according to the percentage of Th2 and Th17 cells in the peripheral blood and by the type of inflammation. The percentage of Th2 and Th17 cells in the peripheral blood was determined by flow cytometry. Serum MBD2, eosinophilic cationic protein and myeloperoxidase were measured by enzyme-linked immunosorbent assay. Correlations of MBD2 expression with clinical parameters were evaluated using Spearman’s rank correlation analysis. Results Serum MBD2 levels were upregulated in patients with severe asthma compared to healthy controls and patients with mild to moderate asthma. MBD2 was also significantly increased in patients with Th17 severe asthma compared to patients with type 2 severe asthma. Furthermore, MBD2 was positively correlated with MPO and Th17 cells but negatively correlated with ECP and Th2 cells in patients with severe asthma. Conclusions These findings suggest that serum MBD2 may be a potential new biomarker for identifying severe asthma, Th17 severe asthma and the type of airway inflammation. However, these findings are still preliminary and need to be further investigated.